The Phenomenon of The Establishment of Baharu Pondoks By Young Ulama As Well As Relationship With The Welfare of The Kelantan Islamic Community and Family - Daud, Mahyudin Bin; Mohamad Salleh, Muhamad Nasir (El-Usrah: Jurnal Hukum Keluarga, 2024)
Kelantan is known as the Serambi Mekah (Veranda of Mecca) due to the many Islamic scholars from the state who studied in Mecca and returned home to establish pondok (traditional Islamic schools). The late 1800s and early 1900s marked a golden age for these educational centers, with over 100 pondoks operating in the state. However, the number began to decline in the mid-20th century for various reasons. Yet, in the early 2000s, Kelantan witnessed the emergence of many new pondoks, with participation reaching 70 during the 2022 gathering of Kelantan pondoks at Pondok Batu Hitam, Pasir Puteh. This phenomenon indicates a significant increase in the establishment of pondoks in Kelantan. Surprisingly, many of these were founded by young scholars who graduated from various Islamic educational institutions worldwide. This article presents a study on the initiatives of these young scholars in establishing pondoks in Kelantan, exploring various aspects and their relationship with religious well-being in the community and families. The study employs a literature review to gather facts about the history and development of pondoks in Kelantan up to the present, as well as field research where the researcher interviewed some of the involved young scholars to obtain data on this phenomenon, alongside elder scholars for their perspectives on the issue. The researcher also consulted the Royal Malaysia Police and the Kelantan Islamic Religious and Customs Council (MAIK) to gather data regarding the religious well-being of the Islamic community and families following the establishment of these educational centers. The findings indicate that the rapid establishment of pondoks is a noble effort by young scholars to propagate Islam in Kelantan by offering alternative education to the Islamic community and families, preparing students for more advanced studies in Islamic institutions worldwide. However, this growth requires oversight from religious authorities and the Kelantan pondok associations to ensure they operate according to traditional pondok systems. The study also received positive feedback from MAIK and the Royal Malaysia Police, indicating that the initiatives of young scholars in establishing new pondoks do not disrupt the religious well-being of the Islamic community and families in Kelantan; rather, they strengthen community unity and instill high values among students according to the teachings of Ahli al-Sunnah wa al-Jamaah in terms of belief, sharia, and ethics.